Sistem Informasi Data Penghasilan Driver Di Projek Official Menggunakan SMS Gateway - aji saputra; zaenanal Hakim; Lili Sujai; Robby Rizky (Admin Situstika, 2024)
PROJEK Official is a company engaged in the field of online transportation facilities in Pandeglang City, Banten, apart from being a means of transportation. delivery of information about driver income which is still submitted manually by coming to the office and asking for information about income and not compatible with confirmation SMS, therefore the results of the analysis that I get will create an information system by having a solution to build